Speech Intelligibility Evaluation of Sound Coding Strategies in Noisy Environments for Thai Cochlear Implant Users - Dachasilaruk, Siriporn; Rungruang, Apichai (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 4 (2018): October-December 2018DO - 10.14456/nujst.2018.29, 2018)
The paper presents the effect of sound coding strategies on speech intelligibility of Thai-speaking cochlear implant (CI) users. Two sound coding strategies, namely continuous interleaved sampling (CIS) and advanced combination encoder (ACE) strategies were evaluated for word recognition. The tested words consisting of monosyllabic and bisyllabic words were corrupted by speech shaped noise and babble noise at SNR levels of 0, 5, 10 and 15 dB. The vocoded speech of clean and noisy words were tested by twelve normal-hearing listeners. The experimental results showed that speech intelligibility of the ACE strategy had higher mean scores than that of the CIS strategy in all tested conditions. The ACE strategy provided a significant speech intelligibility at SNR levels of 5 and 10 dB for monosyllabic words with speech shaped noise and at SNR levels of 0 dB for bisyllabic words with speech shaped noise. In addition, the noisy bisyllabic words provided higher intelligibility performance than the noisy monosyllabic words in all tested conditions. Keywords: cochlear implant, sound coding, speech intelligibility, filter bank, hearing loss